The Effectiveness of Imago Therapy on Anxiety, Sexual Self-Efficacy, and Emotional Expression in Women Affected by Marital Infidelity - Rostami, Narges; Heydari, Behnam; Hosseini, Seyedah Sara (KMAN Counseling & Psychology Nexus, 2024)
The present study aimed to investigate the effectiveness of Imago therapy on anxiety, sexual self-efficacy, and emotional expression in women affected by marital infidelity. This research utilized a quasi-experimental design with a pre-test and post-test control group. The statistical population included all women referred to family counseling centers in Mashhad in 2022. A total of 40 participants were selected from the population using purposive sampling and were randomly assigned to experimental and control groups (17 participants in the experimental group and 23 in the control group). The experimental group received ten 60-minute Imago therapy sessions (two sessions per week). Research instruments included the Beck Anxiety Inventory (BAI) by Beck et al. (1988), the Sexual Self-Efficacy Questionnaire (SSEQ) by Vaziri and Lotfi Kashani (1999), and the Emotional Expression Questionnaire (EEQ) by King and Emmons (1990). Results from covariance analysis indicated that, after controlling for the pre-test effect, there was a significant difference between the mean scores of anxiety, sexual self-efficacy, and emotional expression in the experimental and control groups at the 0.01 level, and this difference was maintained in the follow-up phase. The findings suggest that emotion-based skills provide an effective approach to enhancing meta-emotion and reducing fear of intimacy and hostile attribution.